2021
DOI: 10.3389/fcell.2021.791643
|View full text |Cite
|
Sign up to set email alerts
|

Notoginsenoside R1 Protects Against High Glucose-Induced Cell Injury Through AMPK/Nrf2 and Downstream HO-1 Signaling

Abstract: Notoginsenoside R1 (NGR1), the primary bioactive compound found in Panax notoginseng, is believed to have antihypertrophic and antiapoptotic properties, and has long been used to prevent and treat cardiovascular diseases. However, its potential role in prevention of diabetic cardiomyopathy remains unclear. The present study aimed to investigate the mechanism of NGR1 action in high glucose-induced cell injury. H9c2 cardiomyocytes were cultured in a high-glucose medium as an in-vitro model, and apoptotic cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…At the same time, we found that the myocardial AMPK pathway was significantly activated after DJB surgery, and many studies have shown that activation of the AMPK pathway is very important for the improvement of metabolism [32,33]. Similarly, activation of the AMPK pathway can promote eNOS phosphorylation and improve the antioxidant system [6,[34][35][36], suggesting that improvement of oxidative stress by DJB surgery may depend on the AMPK pathway. To verify the feasibility of the AMPK pathway on the phosphorylation levels of eNOS, SOD2, and NRF2/HO-1, we used an AMPK agonist to stimulate H9C2 cells in the HG+PA environment.…”
Section: Discussionmentioning
confidence: 75%
“…At the same time, we found that the myocardial AMPK pathway was significantly activated after DJB surgery, and many studies have shown that activation of the AMPK pathway is very important for the improvement of metabolism [32,33]. Similarly, activation of the AMPK pathway can promote eNOS phosphorylation and improve the antioxidant system [6,[34][35][36], suggesting that improvement of oxidative stress by DJB surgery may depend on the AMPK pathway. To verify the feasibility of the AMPK pathway on the phosphorylation levels of eNOS, SOD2, and NRF2/HO-1, we used an AMPK agonist to stimulate H9C2 cells in the HG+PA environment.…”
Section: Discussionmentioning
confidence: 75%
“…NGR1 is one of the main active components in P. notoginseng and previous studies have shown that NGR1 could attenuate myocardial injury and reduce myocardial infarct size in an ischemia/reperfusion injury model ( Tong et al, 2019 ), which may be through Nrf2-HO-1 or mTOR induced inflammation and apoptosis signaling pathway ( Du et al, 2021 ; Liu et al, 2021 ). However, its mechanism on AMPK mediated lipotoxicity in AMI-post heart failure has not been described before.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin effectively alleviated oxidative stress, inhibited myocardial cell apoptosis, and improved cardiac remodeling and dysfunction in DCM. Du et al (2021) conducted an in vitro experiment to explore the protective effect of Notoginsenoside R1 (NGR1) against high glucose‐induced myocardial cell injury. The results showed that NGR1 reduced high glucose‐induced H9c2 myocardial cell death, apoptosis, and hypertrophy by upregulating the AMPK/Nrf2 signaling pathway and the expression of HO‐1.…”
Section: Natural Substances Treat Dcm By Targeting Different Pcdsmentioning
confidence: 99%